EFFECT OF FINANCIAL PERFORMANCE AND FOREIGN OWNERSHIP ON COMPANY VALUES - Ana Mardiana; Fransiskus Eduardus Daromes; Joshua Santoso (SIMAK, 2023)
This study aims to examine the effect of financial performance and foreign ownership on firm value (empirical study on LQ 45 index companies in 2017-2019. Financial performance in this study is measured by Return on Equity (ROE) while firm value is measured by Tobin's Q. This type of research is explanatory research and the theory used in this study is Signaling Theory. The population in this study was obtained using a purposive sampling method on the LQ 45 index companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2019 period which were included in the LQ 45 list respectively. The number of samples is 32 companies using secondary data, namely annual reports and financial statements. The analytical method used is multiple linear regression analysis with SPSS (Statistical Product and Service Solutions) tools. The results showed that financial performance had a significant positive effect on firm value. Foreign ownership has a significant positive effect on firm value.